Ultrafine Prussian Blue as a High‐Rate and Long‐Life Sodium‐Ion Battery Cathode. Issue 7 (13th May 2019) - Gong, Wenzhe; Wan, Min; Zeng, Rui; Rao, Zhixiang; Su, Shang; Xue, Lihong; Zhang, Wuxing; Huang, Yunhui
Abstract : Prussian blue analogs (PBAs) have attracted much attention as cathodes in sodium‐ion batteries due to their stable crystalline structure, high theoretical capacities, and facile synthesis. However, PBAs synthesized by the conventional precipitation method usually have the drawbacks of poor rate performance and cycling stability. Herein, the ball‐milling method is developed to prepare the ultrafine high‐quality Prussian blue. Benefited from its good crystallinity and ultrafine particle size of 40 nm, the obtained Na0.9 Fe[Fe(CN)6 ]0.96 exhibits an outstanding cycling stability and rate capability, which can deliver a specific capacity of 106 mAh g −1 at 30 °C, maintaining 80% capacity after 500 cycles at 10 °C. The results show that a size effect can contribute to the enhancement of electrochemical kinetics of PBAs, and the scalable production of high‐performance PBAs can be anticipated based on the ball‐milling method. Abstract : Na0.9 Fe[Fe(CN)6 ]0.96 with a particle size less than 40 nm is synthesized by a dry‐milling method. It exhibits an outstanding rate capability and cycling stability as a cathode for sodium‐ion batteries, which can be ascribed to its high crystallinity, ultrafine particles, and mesoporous structure.